2022
DOI: 10.1093/arclin/acac056
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive and Psychosocial Characteristics of Pediatric Patients With Post-Acute/Long-COVID: A Retrospective Clinical Case Series

Abstract: Objective Studies suggest a large number of patients have persistent symptoms following COVID-19 infection—a condition termed “long COVID.” Although children and parents often report cognitive difficulties after COVID, very few if any studies have been published including neuropsychological testing. Methods A retrospective chart review was completed for the first 18 patients referred for a neuropsychological evaluation from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Nearly 18% of the patients were found to have memory impairment [ 14 ]. Research involving a retrospective chart review of 18 children aged 6-16 years found that 22.2% had memory difficulties [ 15 ]. While not one of the most common cognitive symptoms in children, overall studies show that the clinical manifestation of long COVID is similar in both adult and child populations [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nearly 18% of the patients were found to have memory impairment [ 14 ]. Research involving a retrospective chart review of 18 children aged 6-16 years found that 22.2% had memory difficulties [ 15 ]. While not one of the most common cognitive symptoms in children, overall studies show that the clinical manifestation of long COVID is similar in both adult and child populations [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was estimated that 45% of the patients experienced concentration problems [ 21 ]. A neuropsychological test conducted on 18 patients aged 6 to 16 reported that 83% suffered from attention problems [ 15 ]. A cross-sectional study including children under 18 years diagnosed with COVID-19 found that at least 10% of the patients suffered from a lack of concentration for more than three months after the diagnosis of COVID-19 [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 of the 55 studies included population-based control groups [ 10 , 11 , 19 , 20 , 23 , 24 , 26 , 29 , 33 , 35 , 36 , 38 , 39 , 46 , 47 , 53 , 60 63 , 65 ]. 18 (33%) recruited from a mix of previously hospitalised and non-hospitalised [ 11 , 23 , 26 , 31 , 32 , 35 , 36 , 40 , 41 , 48 , 49 , 51 , 53 , 58 , 61 , 65 , 67 , 71 ], 27 (49%) recruited from non-hospitalised CYP [ 10 , 12 , 19 , 20 , 24 , 27 29 , 33 , 37 , 38 , 45 47 , 52 , 54 57 , 59 , 60 , 62 , 63 ,…”
Section: Resultsmentioning
confidence: 99%
“…Two of the studies used the same population and methodology but presented findings in two publications divided by age group [19,20]. These two publications were Of the 55 included studies, 35 (64%) were cohort studies [10][11][12], 14 (25%) crosssectional studies [19,20,[54][55][56][57][58][59][60][61][62][63][64][65][66], and 6 (11%) were case reports or series [67][68][69][70][71][72]. 20 of the 55 studies included population-based control groups [10,11,19,20,23,24,26,29,33,35,36,38,39,46,47,53,[60][61][62][63]65].…”
Section: Resultsmentioning
confidence: 99%